Leadership and integrity: a study of which legal test best implements Chapter Six of the constitution of Kenya (2010) - Theuri, G. M. (Strathmore University, 2024)
The promulgation of the constitution in 2010 sought to present a clean break from Kenya’s past marred by poor governance consisting of the political use of violence, corruption, tribalism and human rights violations among others. With chapter six therein seeking to set higher standards for persons seeking state office so as to enable good governance, there has been a variance as to what threshold best implements it. Courts have shared divided opinions as to whether to let actions determining lack of integrity rise to a threshold of criminality or not to rise to that threshold or even to look deeply into the facts of each case and determine if the allegations put forward consist of lack of integrity. It is for this reason that this study seeks to establish which test best suits the implementation of the integrity chapter of the constitution. This study was a desk-based project that has mostly relied on qualitative evidence emanating mostly from secondary sources such as research reports, chapters in books, journal articles and case law. It has found that indeed, while there is a need for implementation of chapter six, there is discord as to how it will be implemented. This study therefore recommends the use of the unresolved questions standard which is highest standard, among those that have been put forward, so as to effectively implement chapter six and the high standards therein.
Full - text undergraduate research project